Efeitos regenerativo e analgesico dos extratos aquoso e hidroalcoolico de Caesalpinea ferrea Martius na neuropatia ciática experimental em ratos - Freitas, Maisa Oliveira de (Brasil, 2013)
This study aimed to evaluate the regenerative and analgesic effects of the aqueous and hydroalcoholic extract of Caesalpinia ferrea pods – daily dosage of 300 mg/kg – on experimental sciatic neuropathy and non-neuropathic peripheral pain. An amount of 82 male Wistar rats was used in the experiment. There were 40 neuropathic rats divided in four groups of ten animals. They were treated with aqueous extract, hydroalcoholic extract, saline solution, and one them was pseudo-operated. The other 42 rats were distributed in six groups of seven animals. Three groups were led to writhing test induced by acetic acid administration, and the other three groups to termal test induced by carrageenan. The groups had different treatments with aqueous and hydroalcoholic extract and saline solution. Spontaneous (motor and pain) and induced (hyperalgesia and flare) behavioural studies were conducted. There were not significant difference between the groups treated or not with the extracts. However, in the third week, the induced behaviors of interdigital and lateral pinch presented significant difference between the groups treated with extracts and the ones treated with saline solution, which suggests analgesic effect for this behaviour. The dosage of 300 mg/kg of aqueous and hydroalcoholic extracts of Caesalpinia ferrea pods in the experimental traumatic sciatic neuropathy may not be used as analgesic. This dosage suggests analgesic effects for the induced behaviour of pinch. It shows they may be tested in studies evaluating axonal regeneration. Histological results suggest a higher axonal integrity in animals treated with the extracts, similar to the sham group
Regenerative and analgesic effects of aqueous and hydroalcoholic extracts of Caesalpinia ferrea in experimental sciatic neuropathy in rats
Keywords: Comportamento induzido; Jucá; Hiperalgesia; Alodinia; Nervo ciático; Induced behaviour; Caesalpinia ferrea; Hyperalgesia; Allodynia; sciatic nerve; CIENCIAS AGRARIAS::MEDICINA VETERINARIA